PHYSIOLOGICAL METRICS COLLECTED FROM WEARABLE DEVICES IDENTIFY INFLAMMATORY AND CLINICAL INFLAMMATORY BOWEL DISEASE FLARES. (26th January 2023) - Hirten, Robert; Danieletto, Matteo; Landell, Kyle; Lyu, Jinyan; Whang, Jessica; Zweig, Micol; Helmus, Drew; Rodrigues, Jovita; Bottinger, Erwin; Suarez-Farinas, Mayte; Nadkarni, Girish; Fayad, Zahi; et al.
Abstract: BACKGROUND: Inflammatory bowel disease (IBD) flares are common and unpredictable. Disease monitoring relies on symptom reporting or single timepoint assessments of stool, blood, imaging, or endoscopy—these are inconvenient and invasive and do not always reflect the patient perspective. Advances in wearable technology allow for passive, continuous and non-invasive assessment of physiological metrics including heart rate variability (HRV), the measure of small time differences between each heartbeat, a marker of autonomic nervous system function. Our group has previously demonstrated that changes in autonomic function precedes an IBD flare, can predict psychological state transitions and even identify inflammatory events including SARS-CoV-2 infection. To develop algorithms that can predict IBD flares using wearable device signatures, we launched a national wearable device study called The IBD Forecast study. To assess data quality and feasibility, the first 125 Apple Watch users to enroll were evaluated. METHODS: The IBD Forecast study is a prospective cohort study enrolling anyone ≥18 years of age in the United States (US) with IBD who is willing to (1) use a commercially available wearable device, (2) download our custom eHive app and (3) answer daily survey questions. HRV metrics (mean of the standard deviations of all the NN intervals [SDNN]) were analyzed using a mixed-effect cosigner model that incorporated body mass index, age, and sex. SDNN is a time domain HRV index that reflects both sympathetic and parasympathetic nervous system activity and is calculated from the variance of intervals between adjacent QRS complexes (the normal-to-normal [NN] intervals). Clinical flare was assessed with daily Patient Reported Outcome (PRO)-2 surveys (flare; PRO-2 Crohn's disease >7, PRO-2 ulcerative colitis >2). Inflammatory flare was assessed via patient reported C-reactive protein (CRP), with inflammatory flare defined as >5 mg/L. RESULTS: The first 125 study participants were enrolled across 29 states in the US (Table 1). Circadian features of changes of HRV were modelled (Figure 1). The mesor, or midline of the circadian pattern of the SDNN was higher in those with clinical flare (mean 44.43; 95% CI 41.25-47.75) compared to those in clinical remission (mean 43.03; 95% CI 39.94-46.22) (p<0.004). The mesor of the circadian pattern of the SDNN was lower in those with an inflammatory flare (mean 38.16; 95% CI 30.86-45.72) compared to those with normal inflammatory markers (mean 49.51; 95% CI 43.12-56.26) (p<0.001). CONCLUSIONS: Longitudinally collected HRV metrics from a commonly worn commercial wearable device can identify symptomatic and inflammatory flares. This preliminary analysis of a small proportion of the IBD Forecast Study cohort demonstrates the feasibility of using wearable devices to identify, and may potentially predict, IBD flares.